Regional Economic Outlook, April 2008, Asia and Pacific. (Regional Economic Outlook, 2008)
2008 is shaping up as a challenging year for Asia. Activity in most economies remains fairly buoyant, but growth in the United States and, to a lesser extent, Europe is slowing sharply. Given its extensive trade and financial linkages with the rest of the world, Asia is unlikely to delink. At the same time, inflation pressures are picking up across much of the region. Moreover, the still-unfolding global financial crisis adds a dimension of uncertainty to the picture, and the balance of risks remains on the downside. However, most countries in the region are well-placed to undertake counter-cyclical policies should these prove necessary.